Social determinants of health and asthma. Issue 2 (27th April 2023) - Espaillat, Andre E.; Hernandez, Michelle L.; Burbank, Allison J.
Abstract : Purpose of review: Social determinants of health play a major role in healthcare utilization and outcomes in patients with asthma. Continuing to understand how these complex and interwoven relationships interact to impact patient care will be crucial to creating innovative programmes that address these disparities. Recent findings: The current literature continues to support the association of substandard housing, urban and rural neighbourhoods, and race/ethnicity with poor asthma outcomes. Targeted interventions with community health workers (CHWs), telemedicine and local environmental rectifications can help improve outcomes. Summary: The link between social determinants and poor asthma outcomes continues to be supported by recent literature. These factors are both nonmodifiable and consequences of institutionalized racist policies that require innovative ideas, technologic equity and funding for groups most at risk for poorer outcomes.